Step-by-step explanation:
The question states fine the equation of the normal line of the function
![f(x)=√(x+2),at\text{ }x=-1](https://img.qammunity.org/2023/formulas/mathematics/high-school/zf1o48pi0dzv9tiuv60zvqs9zfqd06p3ux.png)
![f(-1)=y_0=√(-1+2)=√(1)=1](https://img.qammunity.org/2023/formulas/mathematics/high-school/8totpp8ak4pe8l3enuwbb7lg25id82ecoi.png)
The slope os the the normal line at x= x0 is the negative reciprocal of the derivative of the function, evaluated at x=x0
![M(x_0)=-(1)/(f^(\prime)(x_0))](https://img.qammunity.org/2023/formulas/mathematics/high-school/tm0v0t6tr60uy1z3e54rhvknjljcsm1aro.png)
Find the derivative of f(x)
![\begin{gathered} f(x)=√(x+2) \\ f^(\prime)(x)=(x+2)^{(1)/(2)} \\ f^(\prime)(x)=(1)/(2√(x+2)) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/lmedqajlxhrs2n4yuymn6fur0zyvi37yfv.png)
Hence,
![\begin{gathered} M(x_(0))=-(1)/(f^(\prime)(x_(0))) \\ M(x_0)=-2√(x_0+2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/z3isflh5ml727fp49fu217uroa9dbbxsoj.png)
Next, find the slope at the given point.
![\begin{gathered} m=M\left(−1\right)=−2 \\ M(x_0)=-2√(x_0+2) \\ M(-1)=-2√(-1+2) \\ M(-1)=-2√(1) \\ M(-1)=-2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/tnqf58hik0j5dnwhu1qlr9jaw65horg7a7.png)
Finally, the equation of the normal line is
![\begin{gathered} y-y_0=m(x-x_0) \\ y-(1)=-2(x-(-1) \\ y-1=-2(x+1) \\ y-1=-2x-2 \\ y=-2x-2+1 \\ y=-2x-1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/xp2w5p1sjhwhjqmyq3cozbxz15rhnypplj.png)
Hence,
The final answer is
![y=-2x-1](https://img.qammunity.org/2023/formulas/mathematics/college/i7bcvc1vr6bdqthckrpkawv2gvt9ifqrtd.png)
OPTION A is the correct answer